PENGEMBANGAN KOMIK DIGITAL UNTUK MENINGKATKAN PEMAHAMAN MATA PELAJARAN MATEMATIKA MATERI PERTAMBAHAN BAGI SISWA SLOWLEARNER KELAS INKLUSI DI SD AL- FIRDAUS SURAKARTA - Rahmatika; Prihanto; Yusuf Cahyo Nugroho; Nawang Wulan; Alfirdous Geraldi Agviandra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematics is a subject that involves numbers in its learning process. Many students often feel afraid of learning mathematics. This includes slow learner students who, upon hearing the word “mathematics,” tend to perceive it as a difficult subject. Therefore, teachers are required to teach mathematics in a fun, meaningful, and mindful way, in accordance with the principles of deep learning. Teachers need engaging learning media so that slow learner students can learn mathematics through a deep learning approach. One of the enjoyable and meaningful learning media is digital comics. This study on digital comics uses a quantitative method. Data collection was conducted through observation, interviews, and the collection of documents, both photographs and written materials. Data validation was carried out through trustworthiness testing, based on four principles: credibility, transferability, dependability, and confirmability. Based on the collected data and the results of the validation process, it can be concluded that digital comics on addition material in inclusive classrooms help students learn more enjoyably, meaningfully, and deeply, in line with the principles of deep learning